Quality assessment of some specific drug products beyond expiration dates in Saudi Arabia - Haya Aljohar; Ghadah H. altoum; Shahad A. Alkarni; Modhi M. Alburaidi; Samiah Alhabardi (Saudi Pharmaceutical Journal)
Abstract This study investigates the stability of expired emergency medications, dopamine, dexamethasone, naloxone, epinephrine, and dobutamine, beyond their labeled expiration dates in Saudi Arabia. The research addresses a critical issue in healthcare, where short shelf lives lead to substantial medication waste and financial losses. Using validated HPLC methods compliant with USP and BP guidelines, we analyzed the active pharmaceutical ingredient (API) content of these medications post-expiry. Our methodology involved collecting expired samples from public hospitals, which were stored under controlled conditions (protected from light and maintained at a consistent temperature between 15 °C and 30 °C), and conducting physical and chemical analyses to assess their stability. The results indicate that naloxone, dexamethasone, and dobutamine may be viable candidates for shelf-life extension programs, as they retained their API content within acceptable limits. However, epinephrine and dopamine exhibited stability challenges, with significant degradation observed in some samples. The findings suggest that pharmaceuticals can remain effective longer than their expiration dates, potentially reducing waste and improving resource management. However, packaging materials and storage conditions are crucial for maintaining drug stability. This study contributes to the ongoing discussion on shelf-life extension and highlights the need for further research to validate these results across different brands and environmental conditions. The implications of this research are significant, as extending shelf lives could enhance drug availability and reduce shortages, particularly for critical emergency medications like naloxone. Future studies should focus on conducting long-term stability tests under various climatic conditions to support shelf-life extension initiatives effectively.